Optimalisasi Ruang Belajar Ramah Anak di Sekolah Alam Taman Siswa Pesisir Cilincing Jakarta Utara - Tuti Widyaningrum; Januar Agung Saputera; Ansadilla Niar Sitanggang (Universitas 17 Agustus 1945 Jakarta, 2022)
Education is the key to success in improving the quality of human life. With a good education, every person can develop well their capacities so that they can be usefull for themselves and their society. However, not all people are able to access and enjoy the right to education which is the responsibility of the government. Sekolah Alam Taman Siswa Pesisir is here to provide volunteers to help with learning for fishermen's children to learn to read and write and educate national character. However, the learning space facilities for students are still not feasible and unsafe because they are located on the former back of a fishing boat which is already fragile and has no roof. Therefore, it is necessary to improve the learning space facilities so that they become more conducive and optimize to the teaching and learning process so that it is beneficial for students and teachers as well as the community around the school in Sekolah Alam Taman Siswa Pesisir Cilincing, North Jakarta.